Erratum: NAN XIN LIN, XIAO FENG LI, GAO CHENG ZHANG & HUI ZHE FENG (2025) The identity of Peliosanthes revoluta and P. torulosa (Asparagaceae) described from Guangxi, and P. pseudorevoluta, a new species also from Guangxi, China. Phytotaxa 700 (2): 233–242. - Lin, Nan Xin; Li, Xiao Feng; Zhang, Gao Cheng; Feng, Hui Zhe (Phytotaxa, 2025)
N/A